LANGUAGE TESTING, EVALUATION AND FEEDBACK: IELTS PRIMARY TESTS (Conference Zone, 2022)
In order to form the ability to read the original literature on the specialty, to participate in oral communication in a foreign language in the process of training future personnel in the system of higher education in the country and finding the necessary information for scientific purposes, English lessons wishing